MENYIAPKAN MASA DEPAN DI MASA DINI - Putlia, Grace; Sundoro, Hary Saputra; Wijaya, Brendi; Wardhana, Ali; Rowena, Janny; Budi, Budi; Samuel, Samuel; Pipiyen, Pipiyen (Jurnal Pengabdian dan Kewirausahaan, 2019)
Knowing that human resources are important for the progress of a nation, it is necessary to have early preparation in order to be able to foster the future well. Supported also by the third Tri Dharma of Higher Education - Pengabdian Kepada Masyarakat (PKM), which states that the responsibilities of a teacher include transferring, transforming, and applying knowledge from within the campus to the public. Based on this, the University of Bunda Mulia conducted PKM activities by raising the topic "Preparing the Future in the Early Age". The selection of the subject of this research that has been adjusted to the topic is the Bhakti Utama School students. The method used in this PKM is ice breaking, the delivery of material includes lectures, sharing experiences and video playback as well as a question and answer session that results in two-way communication. In short, the material presented is in the form of the importance of money management and preparation for further education, planning provides direction and reduces uncertainty, and how to change bad behavior and habits. Each session is thirty minutes long. This PKM activity is expected to be held again, of course with more varied topics.